Cellular Physiology and Pathophysiology of EAAT Anion Channels - Kovermann, Peter; Engels, Miriam; Müller, Frank; Fahlke, Christoph (Frontiers in Cellular Neuroscience, 2022)
Excitatory amino acid transporters (EAATs) optimize the temporal resolution and energy demand of mammalian excitatory synapses by quickly removing glutamate from the synaptic cleft into surrounding neuronal and glial cells and ensuring low resting glutamate concentrations. In addition to secondary active glutamate transport, EAATs also function as anion channels. The channel function of these transporters is conserved in all homologs ranging from archaebacteria to mammals; however, its physiological roles are insufficiently understood. There are five human EAATs, which differ in their glutamate transport rates. Until recently the high-capacity transporters EAAT1, EAAT2, and EAAT3 were believed to conduct only negligible anion currents, with no obvious function in cell physiology. In contrast, the low-capacity glutamate transporters EAAT4 and EAAT5 are thought to regulate neuronal signaling as glutamate-gated channels. In recent years, new experimental approaches and novel animal models, together with the discovery of a human genetic disease caused by gain-of-function mutations in EAAT anion channels have enabled identification of the first physiological and pathophysiological roles of EAAT anion channels.